THE FORMAL ELEMENTS RESEARCH OF YORUKS TALE - Rushid, Rabie (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
A research on motives and types in stories of nomads living in Stip region of Republic of Macedonia division of Folk Literature. This study has been based on 40 out of 50 stories composed in nomadic villages of Stip area, and these stories have been analyzed differentially. Type numbers of folk tales were given in the work of Antti Aarne-Stith Thompson named “The Types of The Folktale”, and folktales were summarized according to their motif line. Thompson’s fivefold classification (animal tales, original folk tales, vertabras, folk tales with chaining, folk tales which did not take place in the classification) were applied to the study. In addition to my collected study on the stories, I have also analyzed general description of nomads and such topic as a review of their history and life style, and then evaluated general information about the stories, observations during the composition of the stories, and former studies on the stories done in Macedonia.